Efektivitas Peran Tenaga Kesejahteraan Sosial Kecamatan (TKSK) dalam Implementasi Program Keluarga Harapan di Kapanewon Sewon Kabupaten Bantul - Ayu Khairur Rizqiyah; Hanantyo Sri Nugroho (Jurnal Partisipatoris, 2024)
The role of social welfare workers (TKSK) in sub-districts aims to make the distribution of aid from the government to poor families and recipients of the Family Hope Program in Sewon sub-district a success. This is the key to community welfare in Sewon Subdistrict This study aims to determine the role of the sub-district Social Welfare Workers (TKSK) in the implementation of the family hope program to help people with Social Welfare Problems, and to find out what are the supporting and inhibiting factors for the implementation of the role of the District Social Welfare Workers (TKSK) in facilitating People with Social Welfare Problems (PMKS). Data collection techniques in this study used observation, interviews, and documentation. The results showed that the role of the District Social Welfare Workers (TKSK) has not played a good role in facilitating communities with Social Welfare Problems in Sewon sub-district and also assistance. This happened because of the limited ability of the Subdistrict Social Welfare Workers (TKSK) in dealing with communities with Social Welfare Problems in collaboration between the sub-district TKSK Social Welfare Workers and the government, PKH Coordinators, TKSK in the area, and fellow District Social Welfare Workers (TKSK). The form of assistance provided by the Government or Social Services is the Family Hope Program (PKH).